CFD를 이용한 자동차 사이드 미러의 공력특성 연구 - 민선식(Sun-sik Min); 한준규(Jun-Kyu Han); 권기현(Ki Hyun Kwon); 최은동(Eun-Dong Choi); 김문상(Moon-Sang Kim) (항공우주시스템공학회지, 2008)
Aerodynamic characteristics, such as drag and lift, play an important role in automobile design under certain speed conditions. Such characteristics are essential to design an automobile since they are directly related to automobile's performance such as passenger safety and fuel consumption. There is a huge demand for the automobile to have safe performance at high speed. Reduction in drag is also important and it could lead to the solution of air flow induced noise and dust problems. The objective of this research is to find out the aerodynamic differences between conventional side mirror and a modified one using CFD. Although drag generated around a side mirror is only about 7% of the total drag when a car runs, it is very closely related to driver's field of vision and noise generation. CFD simulation of the flowfield around a car side-view mirror was performed using a commercial code; Gambit and FLUENT.